Feminist Pedagogy as Vision in Theological Christian Education: Study on PERUATI (Association of Theologically Educated Women in Indonesia) - Nurseli Debora Manurung (Jurnal Perempuan, 2016)
This paper shows the importance of feminist pedagogy as a vision in Christian theological education. Oppression experiences of women as the root of all of oppression of human and ecology, are approached by liberation and transformative education, for justice and equality. Feminist theology needs a place in theological education and in the church education, thus within feminist perspectivecontexts. The core of the Christian tradition in theology is liberation and transformation. Peruati is presenting this feminist vision. As anassociation of theologically educated women in Indonesia, they come together with theologically educated men for movement, for liberation and transformation. Peruati enter the house-ekklesia as feminist pedagogy. Those are the church education and theological Christian education.